Hubungan antara Dukungan Sosial dengan Hardiness pada Santri Penghafal Al-Qur'an di Aceh Besar - Yasir, Haura Shafiyyah Binti; Mirza, Mirza; Zahrani, Zahrani; Sari, Putri Puspita (Syiah Kuala Psychology Journal, 2025)
Memorizing the Qur'an is an activity that requires perseverance, patience, motivation, and high resilience, especially for students (santri) who has dual rolesas learners in formal education and as students in Islamic boarding schools (pesantren). They are not only required to participate in academic and non-academic activities, but also expected to consistently add to and review their Quranic memorization daily to meet predetermined targets. This condition demands a high level of hardiness in students to cope with various challenges. This study aims to examine the relationship between social supportwhich includes support from parents, teachers, classmates, close friends, and individuals within the school environmentand hardiness among Quran memorizing students (santri) in Aceh Besar. The research subjects consisted of 230 students selected through cluster random sampling and proportionate stratified random sampling techniques. The research instruments used were the Children and Adolescent Social Support Scale (CASSS) and the Dispositional Resilience Scale (DRS-15). Hypothesis testing was conducted using the Pearson Product Moment Correlation. The results showed a correlation coefficient of r=0.329 (p 0.05) for the parental support dimension, r=0.121 (p 0.05) for teacher support, r = 0.277 (p 0.05) for classmate support, r = 0.213 (p 0.05) for close friend support, and r=0.333 (p 0.05) for support from individuals in the school environment. The findings indicate a significant positive relationship between social support from four sourcesparents, classmates, close friends, and individuals within the school environmentand students hardiness. In contrast, teacher support did not show a significant relationship with student hardiness. The higher the level of social support received, the higher the level of hardiness among the Quran memorizing students.Menghafal Al-Quran merupakan aktivitas yang menuntut ketekunan, kesabaran, motivasi, serta daya tahan yang tinggi, terutama bagi santri yang menjalani peran ganda, satu sisi sebagai pelajar di sekolah formal dan di sisi lain menjadi santri di pesantren. Mereka tidak hanya diwajibkan mengikuti kegiatan akademik dan non-akademik, tetapi juga dituntut untuk menambah dan mengulang hafalan Al-Quran setiap hari guna mencapai target yang telah ditetapkan. Kondisi ini menuntut adanya ketangguhan (hardiness) dalam diri santri untuk menghadapi berbagai tantangan. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial, yang mencakup dukungan dari orang tua, guru, teman sekelas, teman dekat, dan orang-orang di lingkungan sekolah dengan hardiness pada santri penghafal Al-Quran di Aceh Besar. Responden penelitian terdiri atas 230 santri yang dipilih menggunakan teknik cluster random sampling dan proportionate stratified random sampling. Instrumen penelitian berupa skala Children and Adolescent Social Support (CASSS) dan Dispositional Resilience Scale (DRS-15). Uji hipotesis dalam penelitian ini menggunakan Pearson Product Moment Correlation, hasilnya menunjukkan nilai koefisien korelasi r=0.329 (p0.05) untuk dimensi orang tua, dimensi guru r=0.121 (p0.05), dimensi teman kelas r=0.277 (p0.05), teman dekat r=0.213 (p0.05) dan orang-orang di sekolah saya r=0.333 (p0.05). Hasil penelitian menunjukkan adanya hubungan positif signifikan antara dukungan sosial dari keempat dimensiyaitu dukungan dari orang tua, teman sekelas, teman dekat, dan orang-orang di lingkungan sekolah dengan hardiness santri. Sebaliknya, dukungan social guru tidak menunjukkan hubungan yang signifikan dengan hardiness santri. Semakin tinggi dukungan sosial yang diterima, semakin tinggi pula tingkat hardiness santri.